Kompetensi dan Komunikasi Sekretaris Hubungannya dengan Kepuasan Kerja Pegawai di Sekretariat DPRD Batang Hari - Eva Setia Rini Damanik; Hoirul Ardani (CITRA EKONOMI, 2022)
This study aims to determine the respondents' responses about the competence and secretarial communication in relation to job satisfaction of the secretariat employees of the Batang Hari Regency DPRD. This research was obtained by distributing questionnaires to employees at the Secretariat of the Regional People's Representative Council of Batanghari Regency.This Research uses quantitative research. The sample in this study is a systematic Random sampling, so taken from a population sample of 102 people, everyone who is in third place will be taken used as samples with a total of 34 people. Data were collected using a questionnaire that had been tested for validity and realibility. The data analysis technique used is Correlaction Pearson test. The result showed that: 1) respondents’s responses to the competence of the Batang Hari Regency DPRD secretariat employees in the competent, 2) respondents’s responses to the communication of secretary at the Batang Hari Regency DPRD secretariat employees in the very good, 3) respondents’s responses to the Job satisfaction of the Batang Hari Regency DPRD secretariat employees in the very satisfied, 4) the relationship of competence and communication on the Job satisfaction of Batang Hari Regency DPRD secretariat employees